Plan de negocios para la creación de una microempresa de procesamiento y comercialización de mariscos en el cantón Buena Fe, año 2014 - Carriel Carpio, María Beatriz (2015)
The present work is aimed at developing BUSINESS PLAN FOR THE CREATION OF A MICRO PROCESSING AND MARKETING OF SEAFOOD IN GOOD FAITH CANTON, PROVINCE OF RIVERS In chapter one, contextualization is discussed, based on the analysis of the current problematic situation, sets out the objectives, assumptions are made and the investigation is warranted. Chapter two discusses the theoretical, legal and conceptual basis, where the most relevant aspects are described and related to the objectives, identifying variables that were used for the development of research. In chapter three methods, techniques, types, sources of information, population and sample are identified. Chapter four details the results of the market study, in which unmet need about the product, supply, pricing and marketing is determined; The technical study identifies the production process microenterprise through the location, size, selection of machinery and equipment, supplies, raw materials, labor, etc.; then the economic study determines revenues, expenditures, financing fixed assets, including demonstrating the feasibility of you dare year life of the project. Finally the financial evaluation conducted demonstrates the feasibility of investment by applying financial index as the NPV POSSITIVE $44.629,67 and TIR 38,83%;concluding with the conclusion and recommendation.